PENERAPAN CI/CD UNTUK OTOMASI DEPLOYMENT APLIKASI BERBASIS WEB MENGGUNAKAN DOCKER DAN GITHUB ACTIONS - Asfin Rizaldy; Yuana, Haris; Romadhona, Rizki Dwi (Software Development, Digital Business Intelligence, and Computer Engineering, 2026)
Manual deployment processes in web applications often require considerable time and are prone to configuration errors. This issue is also present at SMK PGRI Wlingi, which still relies on manual deployment methods, resulting in potential delays and technical difficulties. In some cases, a single deployment may take up to two hours. This study aims to implement deployment automation by applying Continuous Integration, Continuous Delivery, and Continuous Deployment (CI/CD) using Docker and GitHub Actions to the Digiham Sarana application. The research method employed is Design Science Research (DSR), which consists of six main stages: problem identification, objective definition, design and development, demonstration, evaluation, and communication of results. After the automation system was designed and implemented, five rounds of testing were conducted to measure the average deployment duration while evaluating the speed and stability of the process. The results show that the deployment process can be executed automatically without manual intervention, achieving an average time of 4 minutes and 49 seconds. Functional testing using the blackbox method demonstrated 100% accuracy, with all three test scenarios running as expected. System evaluation was also carried out through close beta testing involving four technical users and one expert validator. The evaluation results indicate a feasibility score of 83.33% from technical users and 85.71% from the expert validator.Based on these findings, the system is considered feasible, efficient, and consistent in automating the web application deployment process within the context of SMK PGRI Wlingi.